PENGUATAN LITERASI DIGITAL BAGI GURU-GURU DI SEKOLAH DASAR NEGERI KECAMATAN JORLANG HATARAN KABUPATEN SIMALUNGUN MASA PANDEMI COVID-19 - Purba, Nancy Angelia; Pratiwi Pane, Eva; Riahni Saragih, Vita (Universitas Muhammadiyah Tapanuli Selatan, 2022)
This strengthening aims to improve the skills of teachers at SD Negeri 091488 Bahsampuran in using technology in online and offline learning. This activity is carried out in the form of socialization and training on the use of simple technology with the google domain, namely gmail, googlemeet, googledrive, GCR, and so on that are directly connected to google. The implementation method used is carried out in stages, namely (1) understanding and skill training and assistance to partners, (2) the process of using literacy consists of three stages, namely the process of preparing tools and materials, the process of practical use and (3) strengthening to see the level of skill of each teacher. . Partners in this strengthening are teachers at SD Negeri 091488 Bahsampuran, Jorlang Hataran District, Simalungun Regency with 13 respondents. The results of the evaluation and satisfaction questionnaire given were an average of 63% of teachers at SD Negeri 091488 Bahsampuran said that this activity was very well implemented and easy to implement.Â